A heuristic approach to minimising maximum lateness on a single machine - Calis, Banu; Bulkan, Serol; Tuncer, Ferit (South African Journal of Industrial Engineering, 2015)
This paper focuses on the problem of scheduling on a single machine to minimise the maximum lateness when each job has a different ready time, processing time, and due date. A simple procedure is developed to find a better solution than the early due date (EDD) algorithm. The new algorithm suggested in this paper is called Least Slack Time - Look Ahead (LST-LA), which minimises the maximum lateness problem. Computational results show that when the number of jobs increases, LST-LA outperforms EDD.